2019
DOI: 10.1089/gtmb.2018.0253
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing Across Young Hispanic and Non-Hispanic White Breast Cancer Survivors: Facilitators, Barriers, and Awareness of the Genetic Information Nondiscrimination Act

Abstract: This study compared facilitators and barriers to genetic testing and determined awareness about the Genetic Information Nondiscrimination Act (GINA) across young Hispanic and non-Hispanic white (NHW) breast cancer (BC) survivors. Materials and Methods: Women diagnosed with BC of age £50 years in 2009-2012 were recruited through the Florida State Cancer Registry to complete a questionnaire. Results: There were 1182 participants of which 61% (174/285) of Hispanic patients, and 65% (580/897) of NHW patients had B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 45 publications
(89 reference statements)
2
35
0
Order By: Relevance
“…Results from this study also highlight the potential of the video to target historically identified barriers that Latinas in the U.S face for reception of GCT, including language barriers and suboptimal referrals [16,21,47,69]. Few education materials are available in Spanish, and very few genetic counselors speak Spanish in the US [70,71].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Results from this study also highlight the potential of the video to target historically identified barriers that Latinas in the U.S face for reception of GCT, including language barriers and suboptimal referrals [16,21,47,69]. Few education materials are available in Spanish, and very few genetic counselors speak Spanish in the US [70,71].…”
Section: Discussionmentioning
confidence: 95%
“…At-risk Latina women are significantly less likely to use GCT services compared to NHWs [16,17,18]. Increasing awareness about GCT and HBOC risk is a logical first step in closing this gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer is the leading cause of cancer death in women worldwide, with about 627,000 deaths in 2018 [1]. About 5–10% of all breast cancer is caused by germline variants in BRCA1/2 [2,3]. Moreover, about 50% of hereditary breast cancer (HBC) cases present germline mutations in BRCA genes [2].…”
Section: Introductionmentioning
confidence: 99%